Information Freshness for Vehicles Communications of Safety-critical Vulnerable Road Users. Issue 1 (June 2021) - Mohammed, Saber F.; Ke, Feng; Lee, Yingloong
Abstract: Information freshness is an indicator of the timing of a status update which is of utmost significance for many real-time applications, such as connected vehicles, autonomous vehicles, and sensor networks. The age of information (AoI) metric is useful for quantifying the information freshness for messages delivered to the entities concerned. In this paper, we averaged the peak AoI (PAoI) over time for each vulnerable road user (VRU) in the network with a proposed algorithm namely, priority-based push-out last-generated first-served (PPLGFS) strategy, for safety-critical usage cases to address the issue of maintaining timely VRU status updates across all nearby connected vehicles. A multi-VRU system that supports the cellular network is assumed in which status updates arrive and should be transmitted over the network to the intended vehicle. We model the worst-case information freshness (i.e., PAoI) for VRU-destination vehicle links, using a queuing model with the proposed algorithm to manage the packets on arrival. It gives priority messages which have arrived recently, and blocks stale packets to avoid wasting network resources for the transmission of old information. Results show that the proposed algorithm used with PAoI gradually achieves a better performance than other queuing models as the packets arrival rate increases. Besides, it also enhances the maintenance of timely VRU status updates in the intended vehicle.